Testing protocols for profiling of surfers' anaerobic and aerobic fitness: A review. - Farley, O. R. L.; Abbiss, C. R.; Sheppard, J. M. (Strength and Conditioning Journal, 2016)
Despite the high metabolic demands of surfing, the literature on surfers' aerobic and anaerobic characteristics is limited. Previous studies have used tethered board paddling, arm cranking, swim bench ergometers, and modified kayak ergometers to investigate peak or maximal aerobic capacity. This review includes research investigating surfing-related testing protocols to improve understanding of methods that can be used for the assessment of anaerobic and aerobic fitness profiling of surfers. Tests used to determine anaerobic power output, sprint paddle speed, and aerobic characteristics are included, with reference to the implications and reliability of different protocols and the physiological profile of surfers.